A Detailed Analysis of Nitrates and Nitrites in Groundwater of Ilorin Environs - Akiwumi, Oluwadurotimi O.; Eletta, Omodele A.; Odebunmi, Oluyemi (Challenges and Advances in Chemical Science Vol. 3, 2021)
Over the course of four months, the levels of nitrates and nitrites in drinking water from two local government areas in Ilorin, Kwara State, were assessed using a HACH DR/EL 5 Spectrophotometer. The average nitrate (NO3-N) concentration in the borehole is 0.185 mg/L, while nitrites (NO2-N) concentration is 0.044 mg/L. The mean concentration of nitrate (NO3-N) in the well is 0.915 mg/L, whereas nitrites are 0.087 mg/L. The measured means for both nitrates and nitrites in groundwater, as well as the highest single-point values, are substantially below the WHO MCL (maximum contamination level) of 10.0 mg/L nitrate as NO3-N and 3.0 mg/L nitrite as NO2-N. The results are likewise below the NSDWQ's (Nigerian Standard for Drinking Water Quality) maximum permissible levelsof 50 mg/L nitrate as NO3-N and 0.2 mg/L nitrite as NO2-N.